Corporate Governance- A Critical Analysis of the Effectiveness of Board Diversity in Public Entities in Zimbabwe. A Case of NRZ, Telone, PSMAS and GMB. - Mtandwa, Jacob (BUSE, 2022)
This study was carried out to critically analyse the effectiveness of board diversity in public entities in Zimbabwe a case of NRZ, GMB, TELONE and PSMAS. The gender demographic characteristic of board members was used as the proxies for diversity. The objective of this study was to analyse the effectiveness of board diversity in public entities performance, to determine the challenges associated in board diversity in public entities, to identify the hindrance in achieving board diversity in public entities and to explore ways that can be put in place to improve board diversity in public entities. Explanatory research design was employed by the research and the sample size used was 40 respondents in which purposive sampling were utilized in selecting the sample. Questionnaires were self-administered to the public entities in Zimbabwe namely Telone, PSMAS, NRZ and GMB. The data was presented in form of tables, pie charts and graphs and it was analysed using the SPSS software It was established that board diversity enables improved financial results of business, enables business reputation and creativity leading to better performance, enhance innovation for the business and enables profit making for the organisation. It was therefore recommended policy makers to streamline the board member appointment procedures for public entities to be objective and transparent and not be political by drafting appointment procedures on deciding new polices and the government to enhance compliance by instituting penalties for none compliance. Public entities are vital to the country's economy because of their roles in economic progress, job creation, and economic expansion.
Keywords: Corporate Governance; Board diversity; Corporate Performance; Public Entities